PENERAPAN REALTIME IMAGE CONVERSION PADA GALERY PHOTOGRAPH MENGGUNAKAN ALGORITMA NEAREST NEIGHBOR INTERPOLATION - Bagus Indra Basudewa; Ham Idris Tumenggung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In disseminating information through internet technology, it is generally summarized by visual media, one of the visual media that is often used is a digital image (Image), where the presentation in visual form on an information has a major influence on the reception of information that is spread. However, the problem that is often found in many people is the limited resolution quality of the images available on the Internet. As a result of these problems, the availability of illustration materials is very limited. This is a factor in the loss of productive time for some disseminators of information to find material elsewhere, which may affect the quality of the information provided by the disseminator. The author's role is to design a Realtime Image Conversion application which is translated as an image conversion directly. The Realtime Image Conversion application will apply the Interpolation method using yahoo Nearest Neighbor Interpolation in solving the problem of limited image resolution quality. This application will be designed as a web application to make it easier to access tools from the Realtime Image Conversion application.